How useful is financial statement information as an auxiliary in investment decisions? Evidence from the French stock market - Pedro Miguel Gomes Machado Coimbra (2019)
The following study shows how financial statement information available can be useful for investment decisions. We test the usefulness of financial statement information available from a set of listed companies at the French stock market, as an auxiliary for an investment strategy on the stock market. Taking this on consideration, on this project it will be analysed investment decisions over the French stock market CAC 40. Based on information from Datastream over the balance sheets, income statements and cash flow statements; a logit model will be implemented. The hypothesis of the semi-efficiency of the markets (Fama, 1970) enhance that the financial statement information available cannot used successfully to detect under valuated stocks, therefore any strategy based on that information should not turn out to be profitable systematically. In contrast with this argument, the fundamental analysts believe that may exist errors in short-term that may turn out to be possible to achieve out of the market returns. Therefore by using 51 financial descriptors as input, an investment strategy was built, consisting in setting winning portfolios that will be assigned for a long position, and a set of loser portfolios that will be assigned for a short position. The study will be over 32 non-financial firms listed on the French Stock market index. Financial statement information from 2009 to 2015 will be used for this study predictions on the year of 2016. Using with the accounting descriptors relevant at 10% p-value, the results of the investment strategy for the different periods turn out to be negative, contrasting with the previous results of other studies. These results do not give strength to the hypothesis of the usefulness of financial statement as an auxiliary for investment decisions, as well for the effectiveness of using logit model.